Etika Berkomunikasi di Media Sosial : Perspektif Generasi Z - Ridho Rahmatulloh; Alip Kusuma Wardana; Muhamad Sobahri; Raihan Fariz Syaban; April Laksana (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
The rapid development of information technology has changed the way humans communicate, especially through social media. Generation Z, who grew up in the digital era, has its own characteristics in using social media, including in terms of interacting and communicating. The purpose of this study is to explore the ethics of communicating on social media from the perspective of Generation Z. The main focus is on Generation Z's understanding of ethical values, how they apply them in everyday communication, and their impact on social relationships. A qualitative approach is used in this research method which involves in-depth interviews with a number of informants from Generation Z, as well as analysis of related literature. The study indicates that, although Generation Z